Cover Feature: Highly Fluorescent Pyrido[2, 3‐b]indolizine‐10‐Carbonitriles through Pseudo Three‐Component Reactions of N‐(Cyanomethyl)pyridinium Salts (Eur. J. Org. Chem. 40/2019). Issue 40 (10th October 2019) - Sokolova, Ekaterina A.; Festa, Alexey A.; Golantsov, Nikita E.; Lukonina, Natalia S.; Ioffe, Ilya N.; Varlamov, Alexey V.; Voskressensky, Leonid G.
Abstract : The Cover Feature shows a kaleidoscope, where simple pieces of colored glass turn into beautiful ornaments. In the central part of the figure, the glass beads form a pyrido[2, 3b]indolizine scaffold, which exhibits strong emissive properties. Similarly to glass beads in the kaleidoscope, multicomponent reactions allow one to combine readily available starting materials to obtain complex molecules. The synthesis of the highlighted heterocycle has been achieved through a multicomponent approach. More information can be found in the Full Paper by A. A. Festa, L. G. Voskressensky et al.